Acidificação e reutilização da cama de frango e sua qualidade física, química e microbiológica - Andrade, Ana Claudia Ferreira de (2017)
With the expansion of poultry farming and the improvement of production technology, the poultry chain tends to intensify more and more, and with this there is a worrying factor related to the environmental aspects, which refers to the substrate for the creation of these birds and their destination after Their use in aviaries. Since its indiscriminate disposal can generate contamination of the environment, which implies serious problems of chemical and microbiological contamination of water and soil resources, which can endanger the quality of life of the population. An alternative that aims to reduce this problem is the reuse of the chicken bed for several batches, however it is necessary that the material reused presents health security, so as not to compromise the performance of the next lots created on this substrate. The use of chemical conditioners has been an alternative used to prolong the shelf-life of the aviaries by improving the characteristics of the bed. In this sense, acidifiers have shown good results mainly because they promote pH reduction, volatile ammonia and pathogenic microorganisms. In view of the above, we aimed to discuss the main factors that affect chicken bed quality and the main methods to optimize its use, focusing on the application of chemical conditioners with acidic properties. The aim of Chapter II was to know the effects of the use of acidifier based on activated calcium sulfate and expanded filosilicate in the treatment of chicken litter in several reuses and its effects on the physical, chemical and microbiological properties. Four reuses of the broiler bed of four broiler chickens were evaluated during 42 days of life, with application of acidifier based on activated calcium sulfate and expanded filosilicate. The experimental design was completely randomized in the plot of subdivided plots in time with factorial in plot (2x4), two treatments (acidified and control) and four reutilizations evaluated over time. Environmental and bed quality assessments (physical, chemical and microbiological) were performed at days zero, 1, 14, 28 and 42. Physical parameters were analyzed for superficial and internal temperature and bed humidity. For the chemical parameters, the pH, ammonia, and total nitrogen of the bed were evaluated. For microbiological evaluations, a quantitative analysis was carried out with isolation and counting of total mesophilic bacteria and enterobacteria, and qualitative analysis for the presence or absence of Salmonella sp. The treatment promoted significant differences for bed surface temperature, pH, ammonia, moisture and total bed nitrogen. There were no effects of the acidifier on internal bed temperature and for microbiological analyzes. The acidified bed treatment with activated calcium sulfate and expanded filosilicate was effective in improving the physicochemical parameters of the chicken litter, but it was not sufficient to improve the microbiological characteristics of the litter. The reuse of the bed worsens the physical-chemical and microbiological quality of the same.